Selected case studies regarding research-based education in the area of machine and civil assemblies - Wdowik, Roman; Litwin, Paweł; Bełzo, Artur; Borowiec, Artur; Magdziak, Marek; Ciecińska, Barbara; Markopoulos, Angelos; Azarhoushang, Bahman; Hojati, Faramarz (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2023)
The paper presents selected case studies in the area of research and teaching activities focused on technical assemblies. The aim of the work is to discuss the current trends in assembly-related research activities in partner universities of the EDURES project and to present teaching methodology related to the research. Due to the great importance of research-based education for innovative teaching methodology, research utilization into teaching process is addressed in the paper as a priority of modern teaching, which uses digital platforms and is focused on fast dissemination of the research results among both researchers and higher education students. This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)